Newly Developed TV-Based Cognitive Training Games Improve Car Driving Skills, Cognitive Functions, and Mood in Healthy Older Adults: Evidence From a Randomized Controlled Trial - Nouchi, Rui; Kobayashi, Akiko; Nouchi, Haruka; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2019)
Background Cognitive training at a laboratory improves car driving skills of older car drivers. Nevertheless, it remains unclear whether cognitive training of other types undertaken at home has beneficial effects on driving skills. Using our developed cognitive training games that work on a TV with a set-top box in a person’s home, we investigated effects of 6-week cognitive training on driving skills which assessed with on-road evaluation (primary outcome) and also check the benefit on cognitive functions and emotional states (secondary outcome) in older people. Methods For this double-blinded randomized control trial (RCT), 60 older licensed drivers were assigned randomly to two groups: a cognitive training game for car driving (CTCD) group and an active control cognitive training game (ACT) group. The CTCD, participants played CTCD (processing speed, dual attention, and speed prediction) for 20 min during 5 sessions per week for 6 weeks. The ACT group participants played ACT (select large number, select number from largest to smallest, rock–paper–scissors) for 20 min during 5 sessions per week for 6 weeks. We measured driving skills, several cognitive functions, and emotional states before and after the 6 week intervention period. Results Our main results demonstrated that, compared to ACT, CTCD improved driving skills (adjusted p = 0.034). Moreover, compared to ACT, CTCD improved inhibition (stroop, adjusted p = 0.042: reverse Stroop, adjusted p = 0.043) and processing speed performance (symbol search, adjusted p = 0.049; digit symbol coding, (adjusted p = 0.047). It increased vigor–activity mood scores (adjusted p = 0.041) as measured using the Profile of Mood State. Discussion This randomized controlled trial first provided scientific evidence related to benefits of 6-week CTCD on driving skills, cognitive functions such as processing speed, inhibition, and vigor–activity mood in healthy older people. Our results suggested cognitive training as a useful tool for improving driving skills of older adults. Trial registration This trial was registered in The University Hospital Medical Information Network Clinical Trials Registry (UMIN 000029769). Registered 31 October 2017, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000034010